Insurance Literacy, Risk Knowledge Management, Risk-Taking Propensity and Economic Sustainability among SMEs: The Moderating Effect of Financial Inclusion - Garba, Murtala; Salleh, Fauzilah; Hafiz, Usman Ahmed; Bakar, Nor Mazlina Abu (Journal of Social Economics Research, 2022)
Small and medium enterprises (SMEs) are known worldwide as tools for economic growth and development as they lead to job creation, improved living standards, sustainable development and poverty eradication. However, complicated risks in production, operation, management, and risk-based decision-making in business has troubled the sector. This study examines the moderating effect of financial inclusion on the relationship between insurance literacy, risk knowledge management, risk-taking propensity and economic sustainability of Nigerian SMEs. Data was collected from 370 SMEs registered with the Small and Medium-scale Enterprise Development Agency of Nigeria (SMEDAN) using self-administered questionnaires. The study employs structural equation modelling (SEM) using AMOS 26.0 software for analysis. The study used multi-group analysis to determine the group in which the effect of moderation is more pronounced. The SEM produced a variety of findings; the path coefficients in the model and the results of the hypothesis testing show that insurance literacy (IL) significantly affects economic sustainability (ES). Also, the path coefficient between risk knowledge management (RKM) and economic sustainability shows a positive and significant relation, indicating that risk management (RM) has a significant positive impact on ES. Finally, the results show that risk-taking propensity (RTP) significantly affects ES. The results of the moderation also revealed that financial inclusion moderates the relationship between IL, RM, RTP and ES. However, the multi-group analysis shows that the effect is more pronounced in the ABC group than the NABC group.